Budgetary gap in achievement equality: a multi-site study of success factors of public and private madrasah aliyah in east java - Tobi; Ahmad Ishom Tamimi; Sahro Wardil Lathif; Ah. Zakki Fuad; Masdar Hilmy (At Turots: Jurnal Pendidikan Islam, 2026)
This study examines the political dynamics of Islamic education funding in Indonesia by analyzing the structural disparity between public and private madrasahs and its implications for educational equity. Although the 1975 Joint Decree of Three Ministers formally recognized madrasahs as integral to the national education system, contemporary realities reveal a persistent funding gap that undermines this formal equality. Employing a qualitative comparative multi-site design, this research analyzes secondary data from government reports, institutional documents, and academic literature to compare two leading institutions in Ewast Java. Findings demonstrate that public madrasahs benefit from comprehensive state support through the national budget (APBN), covering teachers’ salaries, infrastructure, and operational costs, while private madrasahs rely on limited government subsidies (BOS funds) and community-based financing mechanisms. Nevertheless, maintains high performance through adaptive management, multi-source funding (BOS, ZIS, CSR, alumni networks), and strong social capital. These findings reveal that institutional resilience and educational quality are not solely determined by financial magnitude but by managerial autonomy, leadership innovation, and community participation. The study argues for a shift toward a performance-based funding policy that values accountability and institutional creativity over administrative status. Strengthening managerial autonomy and establishing a Public–Community Partnership for Education (PCPE) model are proposed as key policy directions for promoting equity and sustainability in Islamic education.